2016
DOI: 10.1007/s12039-016-1214-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antibacterial activity screening of quaternary ammonium derivatives of triazolyl pyranochromenones

Abstract: A series of quaternary ammonium derivatives of triazolyl pyranochromen-2-ones have been synthesized and characterized; their antibacterial potential were investigated against two gram negative (Pseudomonas aeruginosa and Escherichia coli) and two gram positive bacterial strains (Bacillus cereus and Staphylococcus aureus). In order to develop structure-activity relationship (SAR), the effect of varying the substituent (R) at the C-10 position of pyranochromen-2-one as well as the length of the spacer (n) betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Long alkyl chain quaternary ammonium compounds (QACs) exert a broad range of antibacterial activity against Gram-positive and Gram-negative bacteria, some pathogenic species of fungi and protozoa. 15,16 The amphiphilic nature of QACs, are concurrently exploited for their surfactant, preserving and antimicrobial properties in some cosmetic and personal care products. 17,18 Structural aspects and a variety of biological activities of azo compounds and quaternary pyridinium salts were a motivation for the synthesis of five new azo compounds containing long chain alkyl pyridinium salts for the studies of antibacterial and antioxidant properties.…”
Section: * For Correspondencementioning
confidence: 99%
“…Long alkyl chain quaternary ammonium compounds (QACs) exert a broad range of antibacterial activity against Gram-positive and Gram-negative bacteria, some pathogenic species of fungi and protozoa. 15,16 The amphiphilic nature of QACs, are concurrently exploited for their surfactant, preserving and antimicrobial properties in some cosmetic and personal care products. 17,18 Structural aspects and a variety of biological activities of azo compounds and quaternary pyridinium salts were a motivation for the synthesis of five new azo compounds containing long chain alkyl pyridinium salts for the studies of antibacterial and antioxidant properties.…”
Section: * For Correspondencementioning
confidence: 99%
“…To seek for more effective antimicrobial agents, the effect of varying the substituent (R) as well as the length of the spacer (n) between the triazolyl coumarins and quaternary ammonium group on the antibacterial activity of coumarin–1,2,3‐triazole hybrids 6 has been evaluated by Sharma et al . The preliminary results suggested that both the length of spacer (n) and substituents (‐H /‐ OH /‐ OMe) resulted in the variation in the lipophilicity of the hybrids, and this in turn affect the antibacterial activity.…”
Section: Antibacterial and Antifungal Activitiesmentioning
confidence: 99%
“…2H-Chromen-2-one (coumarin) and its derivatives belong to a class of organic compounds possessing a wide range of biological activities (Penta, 2016;Kumar et al, 2018;Fan et al, 2018). Coumarin-triazole hybrids have attracted noticeable attention due to their antibacterial (Kusanur & Kulkarni, 2005;Shi & Zhou, 2011;Sarasija et al, 2012;Kushwaha et al, 2014;Dongamanti et al, 2014;Ferreira et al, 2015;Zayane et al, 2016;Yadav et al, 2017), antifungal (Feng et al, 2008;Kokil et al, 2010;Panda et al, 2012), antimycobacterial (Xu et al, 2017), anti-Alzheimer (Bagheri et al, 2015;Park et al, 2016;Montanari et al, 2016), anti-inflammatory (Sandhya et al, 2011;Stefani et al, 2012;Seerden et al, 2014) and antitumour (Maiti et al, 2013;Rehman et al, 2014;Zhang et al, 2014;Kraljević et al, 2016;Singh et al, 2017;Liu et al, 2017) activities.…”
Section: Introductionmentioning
confidence: 99%